Financial Liberalisation and Currency Demand in Zambia. - Adam, C (1999)
This paper examines the impact of exchange rate and financial sector liberalisation measures implemented in the early 1990s on the private sector's demand for base money in Zambia. Using time-series data I show how the removal of controls on asset markets led to a permanent shift in the demand for narrow money. Linked with an increase in forecast volatility, this structural break appears to have undermined the efficacy of money-based stabilisation efforts in Zambia.